Manfaat Tepung Daun Salam (Syzygiumpolyanthum) Dalam Meningkatkan Kualitas Olahan Telur Itik Lokal - Zasmeli Suhaemi (Fakultas Pertanian Universitas Tamansiswa Padang, 2015)
The aimed of this study was to determine the effect of salam leaves on local duck eggs processed quality. The material used in this study were 90 local duck eggs. The variables measured were the egg cholesterol content, also the taste and aroma of salted egg. This study used an experimental method that uses a completely randomized design with 3x3 factorial and 2 replications. Its used 2 factors of treatments there A and B. For factor A were various of used salam leaves flour (10, 20, and 30 g) and factor B is various of storage time (13, 17 and 21 days). The result showed that more of the addition of flour salam leaf and the longer the storage will reduce the cholesterol content of salted egg. The most level of salam leaf flour (30 g) which storage in 21 days was the least cholesterol content, 385 mg/100 g.